Development New Press Machine using Programmable Logic Controller (International Journal of Engineering and Computer Science, 2013)
The Press Machine is a project that is designing a new way to improve the previous press machines in industries which has a few weaknesses in safety while operating processes. This will create a lot of problem to the operators which have the higher risk to have an accident. The new press machine is a project to improve previous press machine which have weakness in safety while operating it. This matter creates a lot of problem and at the same time the operators and technician have the higher risk to have an accident in industries. The solution for this problem is a development of a new program of machine which running same operation but the machine is more safety and easy to setup when machine pressing the radio panel using external timer. This machine controlled by the Programmable Logic Controller (PLC). It consists of 5 pneumatic cylinders which each cylinder have their own function. This project contains in 2 states of operations which in automatic and manual mode. In automation mode, all the operation will begin automatically after the operators pressed the 2 switch simultaneously. In manual mode, the operator need to press (switch on) in every state condition to complete the operation. That mean, every state operation has its own switch for the operation. The result showed press machine is able to press the component and device, push it to pick up unit then it will be hold by the pickup unit before it placed on the target place. For the future work, this system should be building with a larger machine as the press components. It will give more power to press the device. The suggestion that can carry out from this research is to use a circuit that can make the Direct Current (DC) current more stable and linear. This project uses the DC current from the motorcycle battery because it more safety for this project